1994
DOI: 10.1111/j.1467-8683.1994.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Audit Committees on Bankers’ Perceptions of Auditor Independence

Abstract: Using 20 bankers as subjects, this exploratory study examined the effects of audit committees on bankers' perceptions of auditor independence. Results reject the null hypothesis which suggest that bankers place more reliance on financial statements in considering loan applications given information on the presence of audit committees than given information on their absence. Those bankers given information on the presence of audit committees recommended a lower interest rate premium than those given information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The presence of ACs has been found to create a perception of enhanced auditor independence and more reliable financial reporting among financial statements users (Gwilliam and Kilcommins, 1998). Similarly, a small sample study of 20 bankers considering loan applications has identified greater reliance on financial statements given information on the presence of ACs than given information on their absence (Tsui et al, 1994). It is, however, difficult to draw general conclusions from these exploratory and survey studies.…”
Section: Auditor Independencementioning
confidence: 99%
“…The presence of ACs has been found to create a perception of enhanced auditor independence and more reliable financial reporting among financial statements users (Gwilliam and Kilcommins, 1998). Similarly, a small sample study of 20 bankers considering loan applications has identified greater reliance on financial statements given information on the presence of ACs than given information on their absence (Tsui et al, 1994). It is, however, difficult to draw general conclusions from these exploratory and survey studies.…”
Section: Auditor Independencementioning
confidence: 99%
“…There is evidence that such reassurance allows the company access to resources. Tsui et al (1994) demonstrated that bankers would more readily advance loans where they perceived that auditor independence was assured by the existence of an audit committee.…”
Section: The`performance'of Independence: the Asking Of Questionsmentioning
confidence: 99%
“…The literature on the monitoring and advising functions of corporate boards and their committees has attracted long-standing scholarly interest (Carson, 2002;Conyon, 1994;Hillier et al, 2011;Pascual-Fuster & Crespí-Cladera, 2018;Peterson et al, 2007;Pucheta-Martínez & García-Meca, 2014;Setia-Atmaja, 2009). The monitoring duties of corporate directors include overseeing the financial reporting process that is the specific focus of the audit committee (Chambers, 2005;Guthrie & Turnbull, 1995;Tsui et al, 1994).…”
Section: Audit Committee Characteristics and Frqmentioning
confidence: 99%
“…The literature on the monitoring and advising functions of corporate boards and their committees has attracted long‐standing scholarly interest (Carson, 2002; Conyon, 1994; Hillier et al, 2011; Pascual‐Fuster & Crespí‐Cladera, 2018; Peterson et al, 2007; Pucheta‐Martínez & García‐Meca, 2014; Setia‐Atmaja, 2009). The monitoring duties of corporate directors include overseeing the financial reporting process that is the specific focus of the audit committee (Chambers, 2005; Guthrie & Turnbull, 1995; Tsui et al, 1994). Directive 2014/56/EU of the European Parliament and of the Council points out the importance of the audit committee's oversight role: “Audit committees, or bodies performing an equivalent function within the audited public‐interest entity, have a decisive role to play in contributing to high‐quality statutory audit” (The European Parliament and the Council of the European Union, 2014).…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%